Faith in the Nominalistic Age? The Possible Theological Contribution of Hermeneutics - Grondin, Jean (Religions, 2023)
This paper inquires about the defensibility of spiritual faith in this Nominalistic age, i.e., an age when all reality is reduced to scientifically ascertainable matter and all spiritual realities are deemed to be irreal. This Nominalistic worldview was developed in the late Middle Ages and became one of the major presuppositions of Modernity. It has made it ever more difficult to defend the legitimacy of faith and its objects. It also played an important, albeit seldom recognized, role in the emergence of Hermeneutical thought in the 20th Century. In his strong, if also seldom carefully studied, interpretation of Heidegger’s philosophy, Gadamer saw in the Nominalism of Modernity one of the main challenges to which Heidegger’s thinking wished to respond: the hegemony of the Nominalistic understanding of being would have led to the Nihilism of our technological Age and made the experience of the Divine unthinkable. After recalling the outlines of this interpretation and of the meaning of Nominalism itself, this paper argues that this Nominalism was also one of the main challenges Gadamer wanted to overcome with his Hermeneutics. It discusses how Hermeneutics strives to overcome this Nominalism by calling into question the monopoly of scientific truth (an effort summed up in the title “Truth and Method”) and through its renewed understanding of language as the presentation of Being itself, which goes hand in hand with the rediscovery of the Platonic metaphysics of the Beautiful. Hermeneutics thus shows how something like faith is defensible and thus makes an important theological and metaphysical contribution.